Haemato-immunological responses of Labeo catla (Hamilton, 1822) induced with poly I:C - Panda, Soumya Prasad; Soren, Dhananjay; Das, Basanta Kumar (Journal of the Inland Fisheries Society of India, 2021)
The study was conducted to investigate the effects of polyinosinic: polycytidylic acid (poly I: C) administration on haemato-biochemical parameters of Labeo catla. Fishes (100.12 Â± 6.21g) were acclimatized for 7 days before poly I: C injection. The blood samples were collected on day 1, 2, 3, 4, 5, 7 and 14 after poly I: C treatment. It was observed that the erythrocyte count decreased whereas leucocyte count increased in treated fish throughout the study period. The haematological indices like hemoglobin, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration and platelet count increased in the treatment group up to 3rd day and then gradually declined, however the value in control group did not show any variation throughout the study period. Hematocrit and mean corpuscular volume were reduced as compared to the control group. Biochemical profiles like serum glucose levels were significantly low in treated fish. The total protein increased till the 4th day whereas in control it did not vary significantly. The trend of total protein showed up-regulation whereas albumin showed down-regulated trend. The levels of globulin, urea and cholesterol were significantly higher in poly I:C treated fish as compared to the control. The increase in serum total protein, albumin and globulin in poly I: C injected group indicate augmented immune responses in the treatment group with production of different immune surveillance cells. However, there are needs of furtherÂ analysis towards the identification of cellular responses with different signalling cascades. Key words Poly I: C, haematology, blood, biochemistry parameters, immune response